Blisters on their feet : tales of internally displaced persons in India's North East - Das, Samir Kumar, 1961- (Thousand Oaks ; London : SAGE Publications, 2008)
Proceedings of four workshops organized by the Indian Council of Social Science Research-North Eastern Regional Centre.
Includes bibliographical references and index.
Keywords: Internally displaced persons -- India, Northeastern -- Social conditions; Internally displaced persons -- Government policy -- India, Northeastern; Social conflict -- India, Northeastern; Economic development -- India, Northeastern